A new differential pressure flow meter for measurement of human breath flow: Simulation and experimental investigation. Issue 3 (8th January 2016) - Bridgeman, Devon; Tsow, Francis; Xian, Xiaojun; Forzani, Erica
Abstract : The development and performance characterization of a new differential pressure‐based flow meter for human breath measurements is presented in this article. The device, called a "Confined Pitot Tube, " is comprised of a pipe with an elliptically shaped expansion cavity located in the pipe center, and an elliptical disk inside the expansion cavity. The elliptical disk, named Pitot Tube, is exchangeable, and has different diameters, which are smaller than the diameter of the elliptical cavity. The gap between the disk and the cavity allows the flow of human breath to pass through. The disk causes an obstruction in the flow inside the pipe, but the elliptical cavity provides an expansion for the flow to circulate around the disk, decreasing the overall flow resistance. We characterize the new sensor flow experimentally and theoretically, using Comsol Multiphysics ® software with laminar and turbulent models. We also validate the sensor, using inhalation and exhalation tests and a reference method. © 2016 American Institute of Chemical Engineers AIChE J, 62: 956–964, 2016